Dynamic Assessment Strategies for Enhancing Reading Comprehension and Student Motivation - Farisyah, Ulfi; Jamiu Temitope Sulaimon; Sodiq, Jafar (Universitas PGRI Semarang, 2025)
This study explored the impact of dynamic assessment on students’ reading comprehension and motivation in an Indonesian vocational school. English language teaching in Indonesia faces challenges due to diverse student backgrounds and limited support, which often affects learners' proficiency, especially in reading and speaking. A pre-experimental design was used, involving pre-tests, post-tests, and questionnaires to gather data from 35 students. The data were analyzed using SPSS version 25 and quantitative methods. Results showed a noticeable improvement in students’ reading comprehension scores, increasing from a mean of 82 to 89. Students also reported higher motivation, confidence, and engagement in reading activities. These improvements were linked to the personalized and interactive features of dynamic assessment. The study concludes that dynamic assessment is a promising alternative to traditional assessment methods, as it supports individualized learning and enhances student outcomes in reading comprehension and motivation within vocational education contexts.